Thermal spray coating, thermal spray member, method for forming thermal spray coating, and method for manufacturing thermal spray member

By using materials containing crystal-phase rare earth element particles and rare earth element ammonium fluoride composite salt particles, a rare earth element fluoride film is formed by air plasma dissolution method, which solves the problems of rare earth element oxide residue and oxidation reaction, and improves the quality of the film and the efficiency of the semiconductor manufacturing process.

JP7626260B2Active Publication Date: 2025-02-04SHIN ETSU CHEMICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024001625
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-10
Publication Date
2025-02-04
Estimated Expiration
2041-01-28

AI Technical Summary

Technical Problem

In the prior art, when forming a rare earth element oxide film, it is difficult to effectively inhibit the residual and oxidation reaction of rare earth element oxide, resulting in increased particle generation and affecting the quality of the semiconductor manufacturing process.

Method used

A material containing crystal-phase rare earth element particles and rare earth element ammonium fluoride composite salt particles is used to form a rare earth element fluoride film through air plasma dissolution to control the oxidation reaction and reduce the formation of rare earth element oxides.

Benefits of technology

Effectively inhibit the residual and oxidation reaction of rare earth element oxides, reduce the formation of particles in the film, and improve the quality of the semiconductor manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626260000006
    Figure 0007626260000006
  • Figure 0007626260000007
    Figure 0007626260000007
  • Figure 0007626260000001
    Figure 0007626260000001
Patent Text Reader

Abstract

SOLUTION: To form a coating using a material for deposition including particles including the crystal phase of rare earth element fluoride, particles including the crystal phase of rare earth element oxide and particles including the crystal phase of rare earth element ammonium fluoride double salt or a material for deposition including particles including the crystal phase of rare earth element fluoride and particles including the crystal phase of rare earth element oxide and the crystal phase of rare earth element ammonium fluoride double salt.EFFECT: Since a material for deposition or slurry for deposition can form a rare earth element oxy fluoride thermal spray coating without requiring excessive quantity of heat, especially, when forming a thermal spray coating by thermal spraying using the material for deposition or the slurry for deposition, a rare earth element oxy fluoride thermal spray coating less in rare earth element fluoride or rare earth element oxide can be obtained while suppressing the progress of oxidation reaction caused by thermal spraying heat even in the atmosphere, and coating peeling due to influence on the excessive quantity of heat can be suppressed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermal spray coating that is excellent as a corrosion-resistant coating for semiconductor manufacturing equipment components. and a method for forming the same, and a thermal sprayed member provided with a thermal spray coating and a method for manufacturing the same Regarding. [Background technology]

[0002] In recent years, semiconductor integration has progressed, and the line width formed on a wafer by dry etching is required to be 10 nm or less, and there is a demand for reducing particles generated during the semiconductor manufacturing process. Conventionally, rare earth element oxyhalide coatings formed by air plasma spraying (APS) have been studied as coatings that provide the low particle properties required for corrosion-resistant coatings of semiconductor manufacturing equipment members, and as a thermal spray material for this purpose, for example, International Publication No. 2014 / 002580 (Patent Document 1) discloses a thermal spray material containing yttrium oxyfluoride.

[0003] In response to this, the development of rare earth element oxyfluoride coatings formed by atmospheric suspension plasma spraying (SPS), which is expected to further improve particle reduction properties, is progressing, and as a thermal spray material for this purpose, WO 2015 / 019673 (Patent Document 2) discloses a thermal spraying slurry containing particles containing rare earth element oxyfluoride and a dispersion medium. However, since the thermal spray coating formed by atmospheric suspension plasma spraying is obtained through a high-power thermal spray plume, the oxidation reaction proceeds more in the thermal spray atmosphere under air than in atmospheric plasma spraying, and a large amount of oxide is formed in the obtained thermal spray coating, which is a problem.

[0004] Conventionally, to obtain a thermal spray coating of a rare earth element oxyfluoride, a rare earth element fluoride, a rare earth element oxyfluoride, a rare earth element oxide, etc. have been sprayed alone or in mixture. For example, when a rare earth element fluoride is sprayed by air suspension plasma spraying, a thermal spray coating of a rare earth element oxyfluoride is obtained, but a large amount of the rare earth element fluoride remains in the thermal spray coating. In addition, in the case of a rare earth element oxyfluoride, even if a thermal spray coating of a rare earth element oxyfluoride is obtained, an oxidation reaction proceeds in the atmosphere during the thermal spraying process, and a large amount of rare earth element oxide is by-produced in the thermal spray coating. On the other hand, in the case of a mixture of a rare earth element fluoride and a rare earth element oxyfluoride, or a mixture of a rare earth element fluoride and a rare earth element oxide, it is necessary to perform thermal spraying under high power conditions in order to obtain a thermal spray coating of a rare earth element oxyfluoride by reacting them in an extremely short time during the thermal spraying process, and oxidation of the molten particles proceeds simultaneously with the reaction, resulting in a large amount of rare earth element oxide being by-produced in the coating. These residues and by-products are considered to be one of the causes of particle generation. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 002580 [Patent Document 2] International Publication No. 2015 / 019673 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made in view of the above circumstances, and provides a method for forming a rare earth element oxyfluoride sprayed coating having a low ratio of rare earth element oxide or rare earth element fluoride by suppressing the remaining or by-production of rare earth element oxide or rare earth element fluoride in the sprayed coating, even when the coating is formed in the atmosphere, particularly by atmospheric plasma spraying (APS) or atmospheric suspension plasma spraying (SPS). A thermal spray coating of rare earth element oxyfluoride having a low particle content and containing a low ratio of rare earth element oxide or rare earth element fluoride obtained by thermal spraying a thermal spray material or a slurry for thermal spraying, a method for forming the same, and a thermal sprayed member having the thermal spray coating and a method for manufacturing the same The purpose is to provide 。 [Means for solving the problem]

[0007] As a result of intensive research conducted by the present inventors in order to achieve the above object, A film-forming material including particles including a crystalline phase of a rare earth element fluoride, particles including a crystalline phase of a rare earth element oxide, and particles including a crystalline phase of a rare earth element ammonium fluoride double salt, in particular, a film-forming material in which the particles including a crystalline phase of a rare earth element oxide and the particles including a crystalline phase of a rare earth element ammonium fluoride double salt are dispersed in each other to form composite particles, or A film-forming material comprising particles containing a crystalline phase of a rare earth element fluoride and particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt, in particular a film-forming material in which the particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt form composite particles in which particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt are dispersed on the surface and / or inside of the particles containing the crystalline phase of a rare earth element oxide, with the particles containing the crystalline phase of a rare earth element oxide as a matrix. The inventors have found that such a film-forming material is excellent as a material for use in film formation, and in particular, that it is an excellent thermal spray material capable of easily forming a rare earth element oxyfluoride thermal spray coating containing small amounts of rare earth element fluorides and rare earth element oxides, and that a film-forming slurry containing such a film-forming material is excellent as a thermal spray slurry, which has led to the present invention.

[0008] Accordingly, the present invention provides the following thermal sprayed coating, thermal sprayed member, method for forming a thermal sprayed coating, and method for producing a thermal sprayed member. [1]. In X-ray diffraction using CuKα rays as characteristic X-rays, the diffraction peak of the crystalline phase detected within the diffraction angle range 2θ = 10 to 70° is expressed by the following formula: X ROF =I(ROF) / (I(RF)+I(RO)) (In the formula, I(ROF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxyfluoride, I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by ROF Value is 1.2 or more 2.2 or less A thermal spray coating characterized by: [2]. The thermal spray coating according to [1], characterized in that, among the diffraction peaks of the above-mentioned crystal phase, a diffraction peak assigned to a rare earth element oxyfluoride, a diffraction peak assigned to a rare earth element fluoride, and a diffraction peak assigned to a rare earth element oxide are detected. [3]. In X-ray diffraction using CuKα radiation as the characteristic X-ray, the diffraction peak of the crystalline phase is detected within the diffraction angle range 2θ = 10 to 70°. A diffraction peak assigned to a rare earth element oxyfluoride, a diffraction peak assigned to a rare earth element fluoride, and a diffraction peak assigned to a rare earth element oxide are detected, The following formula X ROF =I(ROF) / (I(RF)+I(RO)) (In the formula, I(ROF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxyfluoride, I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by ROF A thermal spray coating characterized in that the value of is 1.2 or more. [ 4 ].The film thickness is 10 μm or more and 500 μm or less [1] or [3] The thermal spray coating according to claim 1. [ 5 ].On the substrate, [1] or [4] A thermal sprayed member comprising the thermal spray coating according to claim 1. [ 6 ]. It is characterized as being a semiconductor manufacturing equipment component [ 5 ] The thermal sprayed member described in the above. [ 7 (1) A thermal spray material comprising particles including a crystal phase of a rare earth element fluoride, particles including a crystal phase of a rare earth element oxide, and particles including a crystal phase of a rare earth element ammonium fluoride double salt; (2) A thermal spray material comprising particles containing a crystalline phase of a rare earth element fluoride and particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt; (3) A slurry for thermal spraying, comprising a film-forming material including particles including a crystal phase of a rare earth element fluoride, particles including a crystal phase of a rare earth element oxide, and particles including a crystal phase of a rare earth element ammonium fluoride double salt, and a dispersion medium; or (4) A slurry for thermal spraying comprising a film-forming material including particles containing a crystalline phase of a rare earth element fluoride and particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt, and a dispersion medium. A method for forming a thermal sprayed coating, comprising thermally spraying a [ 8 ].On the substrate, (1) A thermal spray material comprising particles including a crystalline phase of a rare earth element fluoride, particles including a crystalline phase of a rare earth element oxide, and particles including a crystalline phase of a rare earth element ammonium fluoride double salt; (2) A thermal spray material comprising particles containing a crystalline phase of a rare earth element fluoride and particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt; (3) A slurry for thermal spraying, comprising a film-forming material including particles including a crystal phase of a rare earth element fluoride, particles including a crystal phase of a rare earth element oxide, and particles including a crystal phase of a rare earth element ammonium fluoride double salt, and a dispersion medium; or (4) A slurry for thermal spraying comprising a film-forming material including particles containing a crystalline phase of a rare earth element fluoride and particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt, and a dispersion medium. A method for producing a thermal sprayed member, comprising thermally spraying a thermal spray coating. The present invention also relates to the following film-forming material, film-forming slurry, thermal sprayed coating, and thermal sprayed member. 1. A film-forming material comprising particles containing a crystalline phase of a rare earth element fluoride, particles containing a crystalline phase of a rare earth element oxide, and particles containing a crystalline phase of a rare earth element ammonium fluoride double salt. 2. The film-forming material according to 1, characterized in that particles containing a crystal phase of the rare earth element oxide and particles containing a crystal phase of the rare earth element ammonium fluoride double salt are dispersed in each other to form composite particles. 3. The film-forming material according to 1 or 2, characterized in that the particles containing a crystalline phase of the rare earth element oxide are rare earth element oxide particles, and the particles containing a crystalline phase of the rare earth element ammonium fluoride double salt are rare earth element ammonium fluoride double salt particles. 4. A film-forming material comprising particles containing a crystal phase of a rare earth element fluoride, and particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt. 5. The film-forming material according to 4, characterized in that particles containing a crystalline phase of the rare earth element oxide and a crystalline phase of the rare earth element ammonium fluoride double salt form composite particles in which particles or layers containing the crystalline phase of the rare earth element ammonium fluoride double salt are dispersed on the surface and / or inside of the particles containing the crystalline phase of the rare earth element oxide, with the particles containing the crystalline phase of the rare earth element oxide as a matrix. 6. The film-forming material according to 5, characterized in that the particles containing a crystalline phase of the rare earth element oxide are rare earth element oxide particles, and the particles or layers containing a crystalline phase of the rare earth element ammonium fluoride double salt are particles or layers of a rare earth element ammonium fluoride double salt. 7. The film-forming material according to any one of 1 to 6, wherein the particles containing a rare earth element fluoride crystal phase are rare earth element fluoride particles. 8. The film-forming material according to any one of 1 to 7, which does not contain a crystal phase of a rare earth element oxyfluoride. 9. The rare earth element ammonium fluoride double salt is (NH4)3R 3 F6, NH4R 3 F4, NH4R 3 2F7 and (NH4)3R 3 2F9 (in the formula, R 3 and each of are one or more elements selected from rare earth elements including Sc and Y. 10. The film-forming material according to any one of 1 to 9, wherein the oxygen content is 0.3 to 10 mass %. 11. In X-ray diffraction using CuKα rays as characteristic X-rays, the diffraction peak of a crystalline phase detected within the diffraction angle range 2θ = 10 to 70° satisfies the following formula: X FO =I(RNF) / (I(RF)+I(RO)) (In the formula, I(RNF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element ammonium fluoride double salt, I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by FO 11. The film-forming material according to any one of 1 to 10, wherein the value of 12. The film-forming material according to any one of 1 to 11, characterized in that the particles containing the crystalline phase of the rare earth element fluoride have an average particle diameter D50(F1) of 0.5 to 10 μm, which is the cumulative 50% diameter (median diameter) in the volume-based particle diameter distribution measured by mixing the particles with 30 mL of pure water and subjecting them to ultrasonic dispersion treatment at 40 W for 1 minute. 13. In the particle size distribution of the particles containing the rare earth element fluoride crystal phase, the following formula is satisfied: P D =(D90(F1)-D10(F1)) / D50(F1) (In the formula, D90(F1) is the cumulative 90% diameter in the volumetric particle size distribution measured after mixing with 30 mL of pure water and ultrasonic dispersion treatment at 40 W for 1 minute, D10(F1) is the cumulative 10% diameter in the volumetric particle size distribution measured after mixing with 30 mL of pure water and ultrasonic dispersion treatment at 40 W for 1 minute, and D50(F1) is the cumulative 50% diameter (median diameter) in the volumetric particle size distribution measured after mixing with 30 mL of pure water and ultrasonic dispersion treatment at 40 W for 1 minute.) P calculated by D 13. The film-forming material according to any one of 1 to 12, wherein the value of 14. The BET specific surface area of ​​the particles containing the above rare earth element fluoride crystal phase is 10 m 2 14. The film-forming material according to any one of 1 to 13, wherein the film-forming material has a molecular weight of 1 / g or less. 15. The loose bulk density of the particles containing the crystal phase of the rare earth fluoride is 0.6 g / cm 315. The film-forming material according to any one of 1 to 14, wherein 16. The film-forming material according to any one of 1 to 15, which is in a powder or granular form. 17. The film-forming material according to 16, characterized in that an average particle size D50 (S0), which is the cumulative 50% diameter (median diameter) in a volume-based particle size distribution, is 10 to 100 μm. 18. A film-forming slurry comprising the film-forming material according to any one of 1 to 15 and a dispersion medium. 19. The film-forming slurry according to 18, wherein the slurry concentration is 10 to 70 mass %. 20. The film-forming slurry according to 18 or 19, wherein the dispersion medium contains a non-aqueous solvent. 21. A film-forming slurry according to any one of 18 to 20, characterized in that the average particle diameter D50 (S1), which is the cumulative 50% diameter (median diameter) in the volume-based particle diameter distribution measured by mixing with 30 mL of pure water and subjecting it to ultrasonic dispersion treatment at 40 W for 1 minute, is 1 to 10 μm. 22. From the average particle diameter D50(S1) (here, D50(S1) is the cumulative 50% diameter (median diameter) in the volume-based particle size distribution measured by mixing with 30 mL of pure water and subjecting the particle to ultrasonic dispersion treatment at 40 W for 1 minute), and the average particle diameter D50(S3) (here, D50(S3) is the cumulative 50% diameter (median diameter) in the volume-based particle size distribution measured by mixing with 30 mL of pure water and subjecting the particle to ultrasonic dispersion treatment at 40 W for 3 minutes), the following formula is used: P SA =D50(S1) / D50(S3) P calculated by SA 22. The film-forming slurry according to any one of 18 to 21, wherein the value of is 1.04 or more. 23. A film-forming slurry according to any one of 18 to 22, characterized in that the film-forming material has an ignition loss of 0.5 mass % or more when measured in air at 500° C. for 2 hours. 24. A film-forming material as described in any one of 1 to 17, which is a thermal spray material. 25. A film-forming slurry according to any one of 18 to 23, which is a slurry for thermal spraying. 26. A thermal spray coating obtained by thermal spraying the film-forming material described in 24 or the film-forming slurry described in 25. 27. A thermal sprayed member comprising the thermal spray coating according to 26 on a substrate. 28. The thermal sprayed member according to claim 27, which is a member for semiconductor manufacturing equipment. Effect of the Invention

[0009] The film-forming material or film-forming slurry of the present invention, in particular, when a thermal sprayed coating is formed by thermal spraying using the film-forming material or film-forming slurry, a rare earth element oxyfluoride thermal sprayed coating can be formed without the need for an excessive amount of heat, so that a rare earth element oxyfluoride thermal sprayed coating containing less rare earth element fluorides and rare earth element oxides can be obtained while suppressing the progress of oxidation reactions due to the heat of thermal spraying even in the atmosphere, and peeling of the coating due to the effects of excessive heat can be suppressed. [Brief description of the drawings]

[0010] [Figure 1] 1 is a scanning electron microscope photograph of the film-forming material obtained in Example 1. [Diagram 2] 1 is an X-ray diffraction profile of the film-forming material obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will now be described in further detail. The film-forming material of the present invention includes a crystal phase of a rare earth element fluoride, a crystal phase of a rare earth element oxide, and a crystal phase of a rare earth element ammonium fluoride double salt. The film-forming material of the present invention can be used in a solid form such as a powder or granule for film formation by thermal spraying, physical vapor deposition (PVD), aerosol deposition (AD), etc., and in the case of thermal spraying, it is suitable for atmospheric plasma spraying (APS). In addition, the film-forming material of the present invention can be made into a film-forming slurry containing a film-forming material and a dispersion medium. When the film-forming material is used in the form of a slurry, it is suitable as a thermal spraying slurry, and the thermal spraying slurry is suitable for atmospheric suspension plasma spraying (SPS).

[0012] The film-forming material of the present invention includes a film-forming material (film-forming material of the first embodiment) that includes particles containing a crystal phase of a rare earth element fluoride, particles containing a crystal phase of a rare earth element oxide, and particles containing a crystal phase of a rare earth element ammonium fluoride double salt. The film-forming material of the first embodiment preferably forms composite particles (composite particles of the first embodiment) in which particles containing a crystal phase of a rare earth element oxide and particles containing a crystal phase of a rare earth element ammonium fluoride double salt are mutually dispersed. In addition, the film-forming material of the first embodiment is preferably a mixture or granulated particles of particles containing a crystal phase of a rare earth element fluoride and the composite particles of the first embodiment. Furthermore, in the case of the film-forming material of the first embodiment, the particles containing a crystalline phase of a rare earth element fluoride are preferably rare earth element fluoride particles, the particles containing a crystalline phase of a rare earth element oxide are preferably rare earth element oxide particles, and the particles containing a crystalline phase of a rare earth element ammonium fluoride double salt are preferably rare earth element ammonium fluoride double salt particles.

[0013] The film-forming material of the present invention also includes a film-forming material (film-forming material of the second embodiment) that includes particles containing a crystal phase of a rare earth element fluoride and particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt. In the film-forming material of the second embodiment, the particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt preferably form composite particles (composite particles of the second embodiment) in which particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt are dispersed on the surface and / or inside of the particles containing a crystal phase of a rare earth element oxide, with the particles containing a crystal phase of a rare earth element oxide as a matrix. In addition, the film-forming material of the second embodiment is preferably a mixture or granulated particles of particles containing a crystal phase of a rare earth element fluoride and the composite particles of the second embodiment. Furthermore, in the case of the film-forming material of the second embodiment, the particles containing a crystalline phase of a rare earth element fluoride are preferably rare earth element fluoride particles, the particles containing a crystalline phase of a rare earth element oxide are preferably rare earth element oxide particles, and the particles or layers containing a crystalline phase of a rare earth element ammonium fluoride double salt are preferably particles or layers of a rare earth element ammonium fluoride double salt.

[0014] Therefore, in both the first and second film-forming materials, the composite particles contain a crystal phase of rare earth oxide and a crystal phase of rare earth fluoride ammonium double salt. In both the first and second film-forming materials, the particles containing the crystal phase of rare earth fluoride are preferably particles composed only of rare earth fluoride without other components, and the crystal phase is preferably particles that are substantially only the crystal phase of rare earth fluoride. In this case, there are advantageously an abundance of particles or layers of rare earth fluoride ammonium double salt in the vicinity of the particles containing the crystal phase of rare earth oxide. Furthermore, in both the first and second embodiments of the film-forming material, the composite particles (the composite particles of the first and second embodiments) may contain small amounts of components other than the rare earth element oxide and the rare earth element ammonium fluoride double salt, but it is preferable that the particles are essentially composed of only the rare earth element oxide and the rare earth element ammonium fluoride double salt, and it is preferable that the crystal phase of the particles is essentially only the crystal phase of the rare earth element oxide and the crystal phase of the rare earth element ammonium fluoride double salt.

[0015] The film-forming material of the present invention preferably does not contain a crystal phase of rare earth element oxyfluoride.Rare earth element oxyfluoride is a compound that is more unstable than rare earth element fluoride or rare earth element oxide, and if the film-forming material contains rare earth element oxyfluoride, for example, when used in thermal spraying, the oxidation reaction of the rare earth element oxyfluoride may proceed preferentially during the thermal spraying process, and the amount of rare earth element oxide in the thermal spray coating obtained by thermal spraying the film-forming material may become large.

[0016] In the present invention, the rare earth element fluoride is R 1 F2, R 1 F3 (where R 1 is one or more elements selected from rare earth elements including Sc and Y. The rare earth element fluoride may be a single type or a mixture of two or more types. 1 may be common to some or all of the rare earth element fluorides or may be different for each rare earth element fluoride.

[0017] In the present invention, the rare earth element oxide is R 2 O, R 2 2O3(R 2 is one or more elements selected from rare earth elements including Sc and Y. The rare earth element oxide may be a single type or a mixture of two or more types. 2 may be common to some or all of the rare earth element oxides, or may be different for each rare earth element oxide.

[0018] In the present invention, the rare earth element ammonium fluoride double salt is (NH4)3R 3 F6, NH4R 3 F4, NH4R 3 2F7, (NH4)3R 3 2F9 (in the formula, R 3 Each of R is at least one selected from rare earth elements including Sc and Y. The rare earth element ammonium fluoride double salt may be a single type or a mixture of two or more types. 3 may be common to some or all of the rare earth element ammonium fluoride double salts, or may be different for each rare earth element ammonium fluoride double salt.

[0019] In the present invention, the rare earth element oxyfluoride is R 4 OF(R 4 1O1F1), R 4 4O3F6, R 4 5O4F7, R 4 6O5F8, R 4 7O6F9, R 4 17 O 14 F 23 , R 4 O2F, R 4 OF2(wherein, R 4 is one or more elements selected from rare earth elements including Sc and Y. The rare earth element oxyfluoride may be a single type or a mixture of two or more types. 4may be common to some or all of the rare earth element oxyfluorides or may be different for each rare earth element oxyfluoride.

[0020] The film-forming material of the present invention may contain, as other components, other rare earth element compounds such as rare earth element hydroxides and rare earth element carbonates or particles thereof, and compounds of other elements or particles thereof, in addition to rare earth element fluorides, rare earth element oxides, and rare earth element ammonium fluoride double salts, as long as the effects of the present invention are not impaired. The content of these other components is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and particularly preferably 1% by mass or less, and most preferably these other components are not substantially contained.

[0021] In addition, as in the film-forming materials of the first and second embodiments, when rare earth element oxide and rare earth element ammonium fluoride double salt are contained as composite particles, rare earth element oxide particles composed only of rare earth element oxide not containing other components, or rare earth element ammonium fluoride double salt particles composed only of rare earth element ammonium fluoride double salt not containing other components may be contained. The total content of rare earth element oxide particles and rare earth element ammonium fluoride double salt particles is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, and particularly preferably 1 mass% or less, relative to the composite particles, but it is most preferable that these rare earth element oxide particles and rare earth element ammonium fluoride double salt particles are not substantially contained.

[0022] In the present invention, the rare earth elements include Sc (scandium), yttrium (Y), and lanthanoids (elements with atomic numbers of 57 to 71). As the rare earth elements, Y, Sc, erbium (Er), and ytterbium (Yb) are particularly preferable.

[0023] The film-forming material of the present invention preferably has an oxygen content of 0.3% by mass or more. If the oxygen content is 0.3% by mass or more, it is advantageous in that, for example, when used in thermal spraying, the amount of rare earth element fluoride in the thermal spray coating obtained by thermal spraying the film-forming material can be reduced, and it is also advantageous in that the surface roughness of the thermal spray coating can be reduced. The oxygen content is more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and particularly preferably 2% by mass or more. On the other hand, the film-forming material of the present invention preferably has an oxygen content of 10% by mass or less. If the oxygen content is 10% by mass or less, it is advantageous in that, for example, when used in thermal spraying, the amount of rare earth element oxide contained in the thermal spray coating obtained by thermal spraying the film-forming material can be reduced. The oxygen content is more preferably 9% by mass or less, even more preferably 8% by mass or less, and particularly preferably 7% by mass or less. In order to set the oxygen content of the film-forming material within the above range, the oxygen content relative to all components constituting the film-forming material may be appropriately adjusted when the film-forming material is produced. Specifically, the ratio of the composite particles (composite particles of the first or second embodiment) in the film-forming material, or the ratio of particles containing a crystal phase of a rare earth oxide in the composite particles may be adjusted.

[0024] The film-forming material of the present invention is characterized in that, in X-ray diffraction using CuKα rays as characteristic X-rays, the diffraction peak of a crystalline phase detected within a diffraction angle range of 2θ=10 to 70° satisfies the following formula: X FO =I(RNF) / (I(RF)+I(RO)) (In the formula, I(RNF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element ammonium fluoride double salt, I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by FOIt is preferable that the value of is 0.01 or more. Here, when two or more compounds are present in each of the rare earth element ammonium fluoride double salt, the rare earth element fluoride, and the rare earth element oxide, I(RNF), I(RF), and I(RO) are the sums of the integrated intensity values ​​of the maximum peaks of the diffraction peaks of the two or more compounds. NH3 gas generated by the decomposition and dissociation of the rare earth element ammonium fluoride double salt has the property of burning at high temperatures, and is not particularly limited, but may be X FO It is believed that the larger the value of X, the more oxygen in the surrounding air is consumed and the more the oxidation of the rare earth element oxyfluoride is suppressed. FO The value of is more preferably 0.02 or more, further preferably 0.05 or more, and particularly preferably 0.08 or more. FO The value of X is preferably 1 or less. FO If the value of X is 1 or less, it is advantageous in that the viscosity increase of the slurry can be suppressed, particularly when the film-forming material is used in the form of a film-forming slurry. FO The value is more preferably 0.8 or less, further preferably 0.6 or less, and particularly preferably 0.4 or less.

[0025] The film-forming material of the present invention is characterized in that, in X-ray diffraction using CuKα rays as characteristic X-rays, the diffraction peak of a crystalline phase detected within a diffraction angle range of 2θ=10 to 70° satisfies the following formula: X F =I(RNF) / I(RF) (In the formula, I(RNF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element ammonium fluoride double salt, and I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride.) X calculated by F It is preferable that the value of is 0.01 or more. Here, when two or more compounds are present in each of the rare earth element ammonium fluoride double salt and the rare earth element fluoride, I(RNF) and I(RF) are the sums of the integrated intensity values ​​of the maximum peaks of the diffraction peaks of each of the two or more compounds. X FIf the value of is 0.01 or more, the ratio of rare earth element ammonium fluoride double salt contained in the film-forming material is high, and when used in thermal spraying, for example, it is effective in suppressing the progress of oxidation reactions during the thermal spraying process. The rare earth element ammonium fluoride double salt decomposes and dissociates in the very short time it exists in the thermal spray plume, thereby generating HF gas and NH3 gas. The generated HF gas is thought to react instantly with the rare earth element oxide contained in the film-forming material, and become a rare earth element oxyfluoride, although there is no particular limitation thereto. X F The value of is more preferably 0.02 or more, further preferably 0.05 or more, and particularly preferably 0.08 or more. F The value of is preferably 1 or less. In the case of a film-forming material containing a rare earth element ammonium fluoride double salt as composite particles with particles containing a crystal phase of a rare earth oxide, when the ratio of the rare earth element ammonium fluoride double salt contained in the rare earth element film-forming material increases, the ratio of the rare earth oxide contained in the rare earth element film-forming material also increases. As a result, for example, when used in thermal spraying, the amount of rare earth element oxide contained in the thermal spray coating obtained by thermal spraying the film-forming material may increase. F The value is more preferably 0.8 or less, further preferably 0.6 or less, and particularly preferably 0.4 or less.

[0026] The film-forming material of the present invention is characterized in that, in X-ray diffraction using CuKα rays as characteristic X-rays, the diffraction peak of a crystalline phase detected within a diffraction angle range of 2θ=10 to 70° satisfies the following formula: X O =I(RNF) / I(RO) (In the formula, I(RNF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element ammonium fluoride double salt, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by OIt is preferable that the value of is 0.01 or more. Here, when two or more compounds are present in each of the rare earth element ammonium fluoride double salt and the rare earth element oxide, I(RNF) and I(RO) are the sums of the integrated intensity values ​​of the maximum peaks of the diffraction peaks of each of the two or more compounds. X O If the value of X is 0.01 or more, the ratio of the rare earth element ammonium fluoride double salt contained in the film-forming material, particularly in the case of a film-forming material containing the rare earth element ammonium fluoride double salt as composite particles with particles containing a rare earth oxide crystal phase, will be high, and for example, when used in thermal spraying, this is effective in increasing the efficiency of the reaction of the rare earth element ammonium fluoride double salt during the thermal spraying process, thereby reducing the amount of rare earth element oxide contained in the thermal spray coating obtained by thermal spraying the film-forming material. O The value of is more preferably 0.02 or more, further preferably 0.05 or more, and particularly preferably 0.08 or more. O The value of X is preferably 1 or less. O If the value of X is 1 or less, for example, when used in thermal spraying, the rare earth element oxide can effectively act as an oxygen source for reacting with a rare earth element fluoride or a rare earth element ammonium fluoride double salt to contain a rare earth element oxyfluoride in the thermal spray coating obtained by thermal spraying the film-forming material. O The value is more preferably 0.8 or less, further preferably 0.6 or less, and particularly preferably 0.4 or less.

[0027] When the rare earth element is, for example, yttrium (Y), the maximum peak of the cubic crystal system of yttrium ammonium fluoride double salt (NH4Y2F7) is not particularly limited, but is generally a diffraction peak assigned to the (541) plane of the crystal lattice. This diffraction peak is usually detected at around 2θ=27.3°. The maximum peak of yttrium fluoride (YF3) is not particularly limited, but is generally a diffraction peak assigned to the (111) plane of the crystal lattice. This diffraction peak is usually detected at around 2θ=27.9°. The maximum peak of yttrium oxide (Y2O3) is not particularly limited, but is generally a diffraction peak assigned to the (222) plane of the crystal lattice. This diffraction peak is usually detected at around 2θ=29.2°.

[0028] The film-forming material of the present invention can be used in a solid form such as powder or granules for film formation by thermal spraying, physical vapor deposition (PVD), aerosol deposition (AD), etc. The rare earth element ammonium fluoride double salt in the film-forming material decomposes at temperatures above 200°C, so the film-forming material is preferably one that has not been fired at a temperature above 200°C. When the film-forming material of the present invention is produced, for example, by granulation, it can be dried at a temperature of 200°C or less. In addition, in the case of a film-forming material produced by granulation, it may contain a binding agent such as a binder that is added as necessary during granulation.

[0029] When the film-forming material of the present invention is used in a solid form such as powder or granules, the average particle diameter D50 (S0), which is the cumulative 50% diameter (median diameter) in the volume-based particle diameter distribution, is preferably 100 μm or less. The average particle diameter D50 (S0) is the average particle diameter measured in the particle diameter distribution of the film-forming material as it is, without performing pretreatment for particle diameter distribution measurement such as ultrasonic dispersion treatment on the film-forming material. The smaller the particle diameter of the film-forming material, for example, when used in thermal spraying, the smaller the splat diameter formed by the molten particles colliding with the substrate or the coating formed on the substrate becomes, and the porosity of the formed thermal spray coating can be reduced, and cracks generated in the splats can be suppressed. The average particle diameter D50 (S0) is more preferably 80 μm or less, even more preferably 60 μm or less, and particularly preferably 50 μm or less. On the other hand, the average particle diameter D50 (S0) is preferably 10 μm or more. The larger the particle size of the coating material, the more advantageous it is in that, for example, when used in thermal spraying, the molten particles have a large momentum and are more likely to collide with a substrate or a coating formed on a substrate to form splats, and that the flowability is improved when the coating material (thermal spray material) is supplied from a thermal spray material supply device to a thermal spray gun. The average particle size D50 (S0) is more preferably 12 μm or more, even more preferably 15 μm or more, and particularly preferably 18 μm or more.

[0030] The film-forming material of the present invention can be dispersed in a dispersion medium and used in film formation in the form of a slurry. When the film-forming material is used in the form of a slurry, the film-forming slurry is suitable as a slurry for thermal spraying. The slurry concentration (content of the film-forming material relative to the entire slurry) is preferably 70% by mass or less. If the content of the film-forming material exceeds 70% by mass, for example, when used in thermal spraying, the slurry may clog the supply device during thermal spraying, and there is a risk that a thermal spray coating cannot be formed. The lower the content of the film-forming material in the film-forming slurry, the more active the movement of particles in the slurry becomes, and the higher the dispersibility becomes. In addition, the lower the content of the film-forming material in the film-forming slurry, the more the fluidity of the slurry improves, making it suitable for slurry supply. The slurry concentration is more preferably 65% ​​by mass or less, even more preferably 60% by mass or less, and particularly preferably 55% by mass or less. When higher fluidity is required, the slurry concentration can be further lowered, and in that case, it is preferably 45 mass% or less, more preferably 40 mass% or less, and even more preferably 35 mass% or less. On the other hand, the slurry concentration is preferably 10 mass% or more. When the content of the film-forming material in the film-forming slurry is higher, for example, when used in thermal spraying, the film-forming speed of the thermal spray coating formed by thermal spraying of the slurry is improved, and productivity can be increased. In addition, the slurry concentration is more preferably 15 mass% or more, even more preferably 20 mass% or more, and particularly preferably 25 mass% or more.

[0031] The film-forming slurry contains a dispersion medium, and the dispersion medium may be used alone or in a mixture of two or more kinds. The dispersion medium is preferably a non-aqueous dispersion medium, that is, a dispersion medium other than water. The non-aqueous dispersion medium is not particularly limited, but examples thereof include alcohol, ether, ester, ketone, etc. More specifically, preferred are monohydric or dihydric alcohols having 2 to 6 carbon atoms such as ethanol and isopropyl alcohol, ethers having 3 to 8 carbon atoms such as ethyl cellosolve, glycol ethers having 4 to 8 carbon atoms such as dimethyl diglycol (DMDG), glycol esters having 4 to 8 carbon atoms such as ethyl cellosolve acetate and butyl cellosolve acetate, and cyclic ketones having 6 to 9 carbon atoms such as isophorone. The non-aqueous dispersion medium is more preferably a water-soluble one that can be mixed with water. When the non-aqueous dispersion medium is used by mixing it with water, water may be contained to the extent that the effect of the present invention is not impaired. The amount of water mixed into the non-aqueous dispersion medium is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less, of the total dispersion medium. However, it is most preferable that the dispersion medium does not substantially contain any dispersion medium other than the non-aqueous dispersion medium (i.e., it does not substantially contain water).

[0032] When the film-forming material of the present invention is used in the form of a slurry, it is preferable that the average particle diameter D50 (S1), which is the cumulative 50% diameter (median diameter) in the volume-based particle diameter distribution measured by mixing with 30 mL of pure water and performing ultrasonic dispersion treatment under conditions of 40 W and 1 minute, is 10 μm or less. The smaller the particle diameter of the film-forming material, for example, when used in thermal spraying, the smaller the splat diameter formed by the molten particles colliding with the substrate or the coating formed on the substrate during thermal spraying, and the lower the porosity of the formed thermal spray coating, and the suppression of cracks generated in the splats. The average particle diameter D50 (S1) is more preferably 9 μm or less, even more preferably 8 μm or less, and particularly preferably 7 μm or less. On the other hand, the average particle diameter D50 (S1) is preferably 1 μm or more. The larger the particle size of the film-forming material, the more advantageous it is in that, for example, when used in thermal spraying, the molten particles have a large momentum and are more likely to collide with the substrate or the coating formed on the substrate to form splats. The average particle size D50 (S1) is more preferably 1.5 μm or more, even more preferably 2 μm or more, and particularly preferably 2.5 μm or more. Thus, it is effective to use a film-forming material with an average particle size D50 (S1) of 1 to 10 μm as a film-forming slurry in order to improve the supplyability of the film-forming material.

[0033] When the film-forming material of the present invention is used in the form of a slurry, the ratio of the average particle diameter D50 (S1) to the average particle diameter D50 (S3), which is the cumulative 50% diameter (median diameter) in the volume-based particle diameter distribution measured by mixing the material in 30 mL of pure water and subjecting it to ultrasonic dispersion treatment at 40 W for 3 minutes, is P SA =D50(S1) / D50(S3) is preferably 1.04 or more. SA The larger the value of P, the more the particles in the film-forming material maintain a moderately aggregated state, and when the film-forming material of the present invention is used in the form of a film-forming slurry, it is possible to prevent compaction due to gravity when precipitation occurs, and to improve the redispersibility of the slurry. SAThe value of is more preferably 1.05 or more, further preferably 1.07 or more, and particularly preferably 1.09 or more. SA The value of is not particularly limited, but from the viewpoint of increasing the fluidity of the slurry, it is preferably 1.3 or less, more preferably 1.28 or less, even more preferably 1.26 or less, and particularly preferably 1.24 or less.

[0034] The film-forming material of the present invention preferably has an ignition loss of 0.5% by mass or more under conditions of 500°C in air for 2 hours. It is usually considered that the smaller the ignition loss, the less the amount of impurities, and therefore the more preferable it is. However, in the film-forming material of the present invention, if the ignition loss under conditions of 500°C in air for 2 hours is 0.5% by mass or more, it is advantageous in that the redispersibility (deflocculation) of the slurry can be improved, particularly when the film-forming material is used as a film-forming slurry. This is not particularly limited, but it is considered that the ammonium fluoride component of the rare earth element ammonium fluoride double salt contained in the film-forming material becomes an energy barrier between particles containing a crystal phase of a rare earth element fluoride, between particles or composite particles containing a crystal phase of a rare earth element oxide, or between particles containing a crystal phase of a rare earth element fluoride and particles or composite particles containing a crystal phase of a rare earth element oxide in the film-forming slurry, preventing aggregation between particles and allowing easy redispersion even after the particles have settled and precipitated. The ignition loss is more preferably 1 mass% or more, even more preferably 2 mass% or more, and particularly preferably 3 mass% or more. On the other hand, the ignition loss is not particularly limited, but from the viewpoint of the effect on the properties of the coating such as the thermal spray coating (reduction of impurities), it is preferably 20 mass% or less, more preferably 15 mass% or less, and particularly preferably 10 mass% or less.

[0035] The particles containing the crystal phase of the rare earth element fluoride contained in the film-forming material of the present invention are preferably mixed with 30 mL of pure water, and subjected to ultrasonic dispersion treatment at 40 W for 1 minute, and the average particle diameter D50 (F1) is the cumulative 50% diameter (median diameter) in the volume-based particle diameter distribution measured. The smaller the particle diameter of the particles containing the crystal phase of the rare earth element fluoride, the smaller the splat diameter formed by the molten particles colliding with the substrate or the coating formed on the substrate when sprayed, for example, when used in thermal spraying, and the porosity of the formed thermal spray coating can be reduced, and cracks generated in the splats can be suppressed. The average particle diameter D50 (F1) is more preferably 9 μm or less, further preferably 8 μm or less, and particularly preferably 7 μm or less. On the other hand, the average particle diameter D50 (F1) is preferably 0.5 μm or more. The larger the particle size of the coating material, the more advantageous it is in that, for example, when used in thermal spraying, the molten particles have a large momentum and are more likely to collide with a substrate or a coating formed on a substrate to form splats. Also, the larger the particle size, the more advantageous it is in that the more convex protrusions formed on the surface of the thermal spray coating can be reduced. The average particle size D50(F1) is more preferably 1 μm or more, even more preferably 1.5 μm or more, and particularly preferably 2 μm or more.

[0036] The particles including the crystal phase of the rare earth element fluoride contained in the film-forming material of the present invention can be calculated by the following formula from the average particle diameter D50(F1), the cumulative 90% diameter D90(F1) in the volume-based particle diameter distribution measured by mixing the particles in 30 mL of pure water and subjecting them to ultrasonic dispersion treatment at 40 W for 1 minute, and the average particle diameter D10(F1) in the volume-based particle diameter distribution measured by mixing the particles in 30 mL of pure water and subjecting them to ultrasonic dispersion treatment at 40 W for 1 minute: P D =(D90(F1)-D10(F1)) / D50(F1) P calculated by D It is preferable that the value of P is 4 or less. DThe smaller the value of P, the sharper the particle size distribution and the more uniform the particle diameter of the material. For example, when used in thermal spraying, it is possible to suppress the variation in the properties of the thermal spray coating obtained by thermal spraying the coating material. D The value of P is more preferably 2 or less, further preferably 1.5 or less, and particularly preferably 1.3 or less. D The lower limit of the value is ideally 0 or more, but in practice it is usually 0.1 or more, preferably 0.5 or more.

[0037] The particles containing a crystal phase of a rare earth element fluoride contained in the film-forming material of the present invention have a particle size distribution in which the average particle size D50(F1) and the average particle size D50(F3), which is the cumulative 50% diameter (median diameter) in the volume-based particle size distribution measured by mixing the particles in 30 mL of pure water and subjecting them to ultrasonic dispersion treatment at 40 W for 3 minutes, are expressed by the following formula: P FA =D50(F1) / D50(F3) P calculated by FA It is preferable that the value of P is 1.05 or less. FA The smaller the value of P, the higher the fluidity of the slurry can be, particularly when the film-forming material is used as a film-forming slurry. FA The value of P is more preferably 1.04 or less, further preferably 1.03 or less, and particularly preferably 1.02 or less. FA The lower limit of the value is ideally 1 or more, but in practice it is usually 1.01 or more.

[0038] The particles containing a crystalline phase of rare earth element fluoride contained in the film-forming material of the present invention have a specific surface area of ​​10 m 2 / g or less is preferable. The specific surface area is usually the BET specific surface area measured by the BET method. The smaller the specific surface area, the more effectively it is possible to reduce, for example, when used in thermal spraying, the number of fine particles that do not fit into the thermal spray frame and adhere to the surface of the formed thermal spray coating, causing particle contamination, and the number of fine particles that evaporate due to excessive thermal spraying heat when they enter the thermal spray plume. The specific surface area is 5 m 2 / g or less is more preferable, and 2m 2 / g or less is more preferable, and 1m 2 On the other hand, the specific surface area is not particularly limited, but is preferably 0.01 m 2 / g or more. The larger the specific surface area, the easier it is for the heat of the spray plume to penetrate into the inside of the particles when thermally sprayed, and when the molten particles collide with a substrate or a coating formed on a substrate to form splats, the denser the coating is, and the stronger the bonds between the splats are. The specific surface area is preferably 0.05 m 2 / g or more is more preferable, and 0.1m 2 More preferably, it is 0.3 m 2 It is particularly preferable that the molecular weight is 1 / g or more.

[0039] The particles containing a crystalline phase of rare earth element fluoride contained in the film-forming material of the present invention have a bulk density of 0.6 g / cm 3 It is preferable that the bulk density is 0.65 g / cm or more. The loose bulk density is usually used as the bulk density. The higher the bulk density, the easier it is to form splats when plasma sprayed, for example, when used in thermal spraying, and the denser the thermal spray coating obtained by spraying the coating material is. In addition, since there is a small amount of gas component contained in the voids in the particles, it is advantageous in that the risk of deterioration of the properties of the thermal spray coating formed can be reduced. The bulk density is 0.65 g / cm 3 More preferably, it is 0.7 g / cm or more. 3 More preferably, it is 0.75 g / cm or more. 3 More preferably, it is equal to or greater than this.

[0040] By spraying the film-forming material or the film-forming slurry of the present invention, a thermal spray coating (surface coating) containing a rare earth element oxyfluoride, which is preferably applied to semiconductor manufacturing equipment members, can be formed on a substrate, for example, directly or via an undercoat (undercoat), and a thermal spray member having a thermal spray coating (surface coating) formed on a substrate, for example, directly or via an undercoat (undercoat), can be manufactured. This thermal spray member is suitable as a semiconductor manufacturing equipment member. The thickness of the thermal spray coating (surface coating) of the present invention is preferably 10 μm or more, more preferably 30 μm or more. The upper limit of the thickness of the thermal spray coating (surface coating) is preferably 500 μm or less, more preferably 300 μm or less.

[0041] The material of the substrate is not particularly limited, but includes metals such as stainless steel, aluminum, nickel, chromium, zinc, and alloys thereof, inorganic compounds (ceramics) such as alumina, zirconia, aluminum nitride, silicon nitride, silicon carbide, and quartz glass, and carbon, and a suitable material is selected depending on the application of the thermal spray member (for example, application for semiconductor manufacturing equipment, etc.). For example, in the case of a substrate made of aluminum metal or an aluminum alloy, a substrate that has been subjected to an acid-resistant alumite treatment is preferred. The shape of the substrate is also not particularly limited, and includes, for example, a planar shape, a cylindrical shape, and the like.

[0042] When forming a thermal spray coating on a substrate, it is preferable to degrease the surface of the substrate on which the thermal spray coating is to be formed with acetone and roughen it with an abrasive such as corundum to increase the surface roughness (surface roughness) Ra. By roughening the substrate, peeling of the coating caused by the difference in thermal expansion coefficient between the thermal spray coating and the substrate after thermal spraying can be effectively suppressed. The degree of roughening may be appropriately adjusted depending on the material of the substrate.

[0043] Before forming the thermal spray coating, an underlayer coating may be formed on the substrate in advance, so that the thermal spray coating can be formed via the underlayer coating. The underlayer coating may have a thickness of, for example, 50 to 300 μm. If the thermal spray coating is formed on the underlayer coating, preferably in contact with the underlayer coating, the underlayer coating can be formed as the underlayer coating and the thermal spray coating can be formed as the surface coating, so that the coating formed on the substrate can be a coating with a multi-layer structure.

[0044] Examples of the material for the undercoat include rare earth oxides, rare earth fluorides, and rare earth oxyfluorides. Examples of the rare earth elements constituting the material for the undercoat include the same rare earth elements as those in the film-forming material. The undercoat can be formed by spraying, such as atmospheric plasma spraying at normal pressure and suspension plasma spraying.

[0045] The porosity of the undercoat is preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less. The lower limit of the porosity is not particularly limited, but is usually 0.1% or more. The surface roughness (surface roughness) Ra of the undercoat is preferably 10 μm or less, more preferably 6 μm or less. The lower limit of the surface roughness (surface roughness) Ra is preferably lower, but is usually 0.1 μm or more. It is preferable to form a thermal spray coating as a surface layer coating on an undercoat with a low surface roughness (surface roughness) Ra, preferably in contact with the undercoat, because the surface roughness (surface roughness) Ra of the surface layer coating can also be reduced.

[0046] The method for forming the undercoat having such low porosity and low surface roughness (surface roughness) Ra is not particularly limited. For example, a single particle powder or granulated thermal spray powder having an average particle diameter D50 of 0.5 μm or more, preferably 1 μm or more, and 50 μm or less, preferably 30 μm or less, is used as a raw material, and the particles are sufficiently melted by plasma spraying, detonation spraying, or the like to perform thermal spraying, thereby forming a dense undercoat having low porosity and surface roughness (surface roughness) Ra. Here, the single particle powder means a powder of particles having a dense content in the form of a spherical powder, an angular powder, a pulverized powder, or the like. When the single particle powder is used, since the single particle powder is a powder composed of fine particles having a smaller particle diameter than the granulated thermal spray powder but having a dense content, a undercoat having a small splat diameter and suppressed cracking can be formed.

[0047] In addition, the surface roughness (Ra) of the base coating can be reduced by surface treatments such as mechanical polishing (surface grinding, inner cylinder processing, mirror finishing, etc.), blasting with microbeads, and hand polishing with a diamond pad.

[0048] The thermal spray coating of the present invention has a diffraction peak of a crystalline phase detected within a diffraction angle range of 2θ=10 to 70° in X-ray diffraction using CuKα rays as characteristic X-rays, which corresponds to the following formula: X ROF =I(ROF) / (I(RF)+I(RO)) (In the formula, I(ROF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxyfluoride, I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by ROF It is preferable that the value of is 1.2 or more. Here, when two or more compounds are present in each of the rare earth element oxyfluoride, rare earth element fluoride, and rare earth element oxide, I(ROF), I(RF), and I(RO) are the sums of the integrated intensity values ​​of the maximum peaks of the diffraction peaks of each of the two or more compounds. X ROFThe larger the value of X, the higher the ratio of rare earth element oxyfluorides present in the thermal spray coating, and the lower the ratio of rare earth element fluorides and rare earth element oxides, which is advantageous from the standpoint of particle resistance. ROF The value is more preferably 1.4 or more, further preferably 1.6 or more, and particularly preferably 1.8 or more.

[0049] When the rare earth element is, for example, yttrium (Y), the maximum peak of the rhombohedral crystal system of yttrium oxyfluoride (YOF(Y1O1F1)) is not particularly limited, but is generally a diffraction peak that is assigned to the (012) plane of the crystal lattice. This diffraction peak is usually detected at around 2θ=28.7°. In addition, the maximum peak of the orthorhombic crystal system of yttrium oxyfluoride (Y5O4F7) is not particularly limited, but is generally a diffraction peak that is assigned to the (151) plane of the crystal lattice. These diffraction peaks are usually detected at around 2θ=28.1°.

[0050] The method for forming the thermal spray coating of the present invention is not particularly limited, but atmospheric plasma spraying (APS) and atmospheric suspension plasma spraying (SPS) are preferred.

[0051] The plasma gas used to form plasma in atmospheric plasma spraying includes, but is not limited to, argon gas alone, nitrogen gas alone, and a mixed gas of two or more selected from argon gas, hydrogen gas, helium gas, and nitrogen gas. The spraying distance in atmospheric plasma spraying is preferably 150 mm or less. As the spraying distance becomes shorter, the deposition rate of the sprayed coating increases, the hardness increases, and the porosity decreases. The spraying distance is more preferably 140 mm or less, and even more preferably 130 mm or less. The lower limit of the spraying distance is not particularly limited, but is preferably 50 mm or more, more preferably 60 mm or more, and even more preferably 70 mm or more.

[0052] The plasma gas used to form plasma in suspension plasma spraying may be a mixed gas of two or more selected from argon gas, hydrogen gas, helium gas, and nitrogen gas, and more preferably a mixed gas of three types of argon gas, hydrogen gas, and nitrogen gas, or a mixed gas of four types of argon gas, hydrogen gas, helium gas, and nitrogen gas, but is not particularly limited. The spraying distance in suspension plasma spraying is preferably 100 mm or less. As the spraying distance becomes shorter, the deposition rate of the sprayed coating improves, the hardness increases, and the porosity decreases. The spraying distance is more preferably 90 mm or less, and even more preferably 80 mm or less. The lower limit of the spraying distance is not particularly limited, but is preferably 50 mm or more, more preferably 55 mm or more, and even more preferably 60 mm or more.

[0053] When forming a thermal spray coating on a substrate or a coating (undercoating) formed on a substrate, it is preferable to perform thermal spraying while cooling the substrate, the coating (undercoating) formed on the substrate, and further the thermal spray coating (surface coating) to be formed. Examples of cooling methods include air cooling and water cooling.

[0054] In particular, the substrate temperature during thermal spraying, or the substrate and the coating formed on the substrate, is preferably 200°C or lower. The lower the temperature, the more likely it is that damage or deformation of the substrate, or the substrate and the coating formed on the substrate, caused by heat can be prevented. In addition, the lower the temperature, the more likely it is that thermal stress can be suppressed, and peeling can be prevented between the substrate and the thermal spray coating formed, or between the coating formed on the substrate (base coating) and the thermal spray coating formed. The substrate temperature during thermal spraying, or the substrate temperature during thermal spraying, is more preferably 180°C or lower, and even more preferably 150°C or lower. This temperature can be achieved by controlling the cooling capacity.

[0055] The substrate temperature during thermal spraying, or the substrate temperature of the substrate and the coating formed on the substrate, is preferably 50° C. or higher. The higher the temperature, the stronger the bond between the substrate and the thermal spray coating formed, or between the coating formed on the substrate (base coating) and the thermal spray coating formed (surface coating), making it possible to make the thermal spray coating denser. The substrate temperature during thermal spraying, or the substrate temperature of the substrate and the coating formed on the substrate, is more preferably 60° C. or higher, and even more preferably 80° C. or higher.

[0056] Other spraying conditions such as the supply rate of the film-forming material (film-forming slurry), the amount of gas supplied, and the applied power (current value, voltage value) in plasma spraying are not particularly limited, and conventionally known conditions can be applied, and may be appropriately set depending on the substrate, the film-forming material (film-forming slurry), the application of the resulting sprayed member, etc. By using the film-forming material or film-forming slurry of the present invention, the desired sprayed coating can be obtained without the need for excessive applied power.

[0057] In particular, when a thermal spray coating is directly formed on a substrate, as described above, the surface roughness (surface roughness) Ra of the substrate surface on which the thermal spray coating is formed is increased, and further, the substrate temperature is set to the above-mentioned temperature, so that a thermal spray coating that is less likely to peel off and has a higher hardness and density can be formed. In this case, the surface roughness (surface roughness) Ra of the formed thermal spray coating tends to be high, so by lowering the surface roughness (surface roughness) Ra by surface processing such as mechanical polishing (surface grinding, inner cylinder processing, mirror processing, etc.), blasting using microbeads, or manual polishing using a diamond pad, it is possible to form a lubricating thermal spray coating that is less likely to peel off, has a higher hardness, is denser, and has a lower surface roughness (surface roughness) Ra. EXAMPLES

[0058] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0059] [Example 1] [Production of yttrium fluoride particles] A 2 mol / L yttrium nitrate aqueous solution equivalent to 2 mol of yttrium nitrate was heated to 50°C, and a 12 mol / L ammonium fluoride aqueous solution equivalent to 7 mol of ammonium fluoride was added to the heated yttrium nitrate aqueous solution, mixed, and the temperature was maintained at 50°C and stirred for 1 hour. The resulting precipitate was filtered, washed, and then dried at 70°C for 24 hours to obtain an yttrium fluoride ammonium double salt. Next, the obtained yttrium fluoride ammonium double salt was fired at 850°C for 4 hours using a tubular furnace under a nitrogen gas atmosphere, and then pulverized with a jet mill to obtain yttrium fluoride particles.

[0060] [Evaluation of physical properties of yttrium fluoride particles] 0.1 g of the obtained yttrium fluoride particles was mixed with 30 mL of pure water in a glass beaker with a maximum scale volume of 30 mL, and ultrasonic dispersion treatment was performed under conditions of 40 W and 1 minute, and the average particle diameter D50 (F1), cumulative 90% diameter D90 (F1), and cumulative 10% diameter D10 (F1) in the volume-based particle diameter distribution were measured. In addition, 0.1 g of the obtained yttrium fluoride particles was mixed with 30 mL of pure water in a glass beaker with a maximum scale volume of 30 mL, and ultrasonic dispersion treatment was performed under conditions of 40 W and 3 minutes, and the average particle diameter D50 (F3) in the volume-based particle diameter distribution was measured. From these results, P D = (D90(F1)-D10(F1)) / D50(F1), and P FA =D50(F1) / D50(F3) The values ​​of were calculated. In addition, the BET specific surface area and loose bulk density were measured. The results are shown in Table 1. Details of each measurement and analysis will be described later.

[0061] [Production of composite particles] 5 mol of yttrium oxide particles having a cumulative 50% diameter (median diameter) of 2 μm in the volume-based particle diameter distribution were added to pure water and stirred to prepare a slurry with an yttrium oxide particle concentration of 20 mass %. 12 mol of acidic ammonium fluoride was added to the obtained slurry and aged at 50° C. for 3 hours. The obtained particles were filtered, washed, and then dried at 70° C. to obtain composite particles containing yttrium oxide and ammonium yttrium fluoride double salt.

[0062] [Production of film-forming materials] The yttrium fluoride particles produced by the above method and composite particles were mixed in a mass ratio of yttrium fluoride particles:composite particles=40:60 to obtain a film-forming material.

[0063] [Evaluation of physical properties of film-forming materials] For the obtained film-forming material, the crystal phase was identified from the diffraction peaks detected within the diffraction angle range of 2θ = 10 to 70° by X-ray diffraction (XRD) using CuKα rays as characteristic X-rays, the crystal structure was analyzed, the maximum peak of each crystal phase component was specified, and the integrated intensity value I (RNF) of the maximum peak of the diffraction peaks attributable to the rare earth element ammonium fluoride double salt, the integrated intensity value I (RF) of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and the integrated intensity value I (RO) of the maximum peak of the diffraction peaks attributable to the rare earth element oxide were calculated. In addition, from these results, X FO =I(RNF) / (I(RF)+I(RO)), X F = I(RNF) / I(RF), and X O =I(RNF) / I(RO) The value was calculated.

[0064] X-ray diffraction was measured using an X-ray diffraction measuring device X'Pert PRO / MPD (Malvern Panalytical), and the crystal phase was identified and the integrated intensity was calculated using analysis software HighScore Plus (Malvern Panalytical). The measurement conditions were: characteristic X-ray: CuKα (tube voltage: 45 kV, tube current: 40 mA), scanning range: 2θ = 5 to 70°, step size: 0.0167113°, time per step: 13.970 seconds, scan speed: 0.151921° / second.

[0065] The obtained film-forming material was subjected to measurement of ignition loss in air at 500°C for 2 hours. The oxygen content was also measured. Furthermore, 0.1 g of the obtained film-forming material was mixed with 30 mL of pure water in a glass beaker with a maximum graduated volume of 30 mL, and ultrasonically dispersed at 40 W for 1 minute, and the average particle diameter D50 (S1) in the volume-based particle diameter distribution was measured. Furthermore, 0.1 g of the obtained film-forming material was mixed with 30 mL of pure water in a glass beaker with a maximum graduated volume of 30 mL, and ultrasonically dispersed at 40 W for 3 minutes, and the average particle diameter D50 (S3) in the volume-based particle diameter distribution was measured. From these results, the ratio between the two P SA =D50(S1) / D50(S3) was calculated. The results are shown in Table 2. A scanning electron microscope photograph of the film-forming material obtained in Example 1 is shown in Fig. 1, and an X-ray diffraction profile is shown in Fig. 2. Details of each measurement and analysis will be described later.

[0066] [Production of film-forming slurry] The film-forming material produced by the above method was mixed with a dispersion medium and dispersed to obtain a film-forming slurry. The slurry concentration and the dispersion medium used are shown in Table 3.

[0067] [Evaluation of the physical properties of slurry for film formation] The viscosity and pH of the resulting slurry were measured, and the results are shown in Table 3. Details of the viscosity measurement will be described later.

[0068] [Example 2] [Production of yttrium fluoride particles] Yttrium fluoride particles were obtained in the same manner as in Example 1, except that the obtained yttrium ammonium fluoride double salt was fired at 800° C. for 2 hours.

[0069] [Evaluation of physical properties of yttrium fluoride particles] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0070] [Production of composite particles] Composite particles were obtained in the same manner as in Example 1, except that yttrium oxide particles having a cumulative 50% diameter (median diameter) in the volume-based particle diameter distribution of 1 μm were used as the yttrium oxide particles.

[0071] [Production of film-forming materials] The yttrium fluoride particles produced by the above method and composite particles were mixed in a mass ratio of yttrium fluoride particles:composite particles=45:55 to obtain a film-forming material.

[0072] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0073] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0074] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0075] [Example 3] [Production of yttrium fluoride particles] The obtained yttrium fluoride ammonium double salt was calcined at 440° C. for 2 hours and crushed with a hammer mill, and other procedures were carried out in the same manner as in Example 1 to obtain yttrium fluoride particles.

[0076] [Evaluation of physical properties of yttrium fluoride particles] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0077] [Production of composite particles] Composite particles were obtained in the same manner as in Example 1, except that the amount of acidic ammonium fluoride was 7 mol.

[0078] [Production of film-forming materials] The yttrium fluoride particles produced by the above method and the composite particles were dispersed and mixed in water in a mass ratio of yttrium fluoride particles:composite particles = 50:50, and carboxymethyl cellulose was added as a binder to prepare a slurry. The obtained slurry was granulated using a spray dryer to obtain a granular film-forming material.

[0079] [Evaluation of physical properties of film-forming materials] Measurement of average particle size D50 (S1) and average particle size D50 (S3), and P SA Instead of calculating the value of D50(S0), the average particle size D50(S0) in the volume-based particle size distribution was measured without ultrasonic dispersion treatment. Except for this, the same procedure as in Example 1 was carried out. The results are shown in Table 2.

[0080] [Example 4] [Production of yttrium fluoride particles] Yttrium fluoride particles were obtained in the same manner as in Example 1, except that the obtained yttrium ammonium fluoride double salt was calcined at 950° C. for 2 hours.

[0081] [Evaluation of physical properties of yttrium fluoride particles] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0082] [Production of composite particles] Composite particles were obtained in the same manner as in Example 1, except that the amount of acidic ammonium fluoride was 7 mol.

[0083] [Production of film-forming materials] The yttrium fluoride particles produced by the above method and composite particles were mixed in a mass ratio of yttrium fluoride particles:composite particles=60:40 to obtain a film-forming material.

[0084] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0085] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0086] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0087] [Example 5] [Production of ytterbium fluoride particles] A 2 mol / L ytterbium nitrate aqueous solution equivalent to 2 mol of ytterbium nitrate was heated to 50°C, and a 12 mol / L ammonium fluoride aqueous solution equivalent to 7 mol of ammonium fluoride was added to the heated ytterbium nitrate aqueous solution, mixed, and the temperature was maintained at 50°C and stirred for 1 hour. The resulting precipitate was filtered, washed, and then dried at 70°C for 24 hours to obtain an ytterbium fluoride ammonium double salt. Next, the obtained ytterbium fluoride ammonium double salt was fired at 900°C for 2 hours using a tubular furnace under a nitrogen gas atmosphere, and then pulverized with a jet mill to obtain ytterbium fluoride particles.

[0088] [Evaluation of physical properties of ytterbium fluoride particles] The physical properties of the yttrium fluoride particles were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0089] [Production of composite particles] 5 mol of ytterbium oxide particles having a cumulative 50% diameter (median diameter) of 1 μm in the volume-based particle diameter distribution were added to pure water and stirred to prepare a slurry with an ytterbium oxide particle concentration of 20 mass %. 10 mol of acidic ammonium fluoride was added to the obtained slurry and aged at 50° C. for 3 hours. The obtained particles were filtered, washed, and then dried at 70° C. to obtain composite particles containing ytterbium oxide and ammonium ytterbium fluoride double salt.

[0090] [Production of film-forming materials] The ytterbium fluoride particles produced by the above method and composite particles were mixed in a mass ratio of ytterbium fluoride particles:composite particles=65:35 to obtain a film-forming material.

[0091] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0092] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0093] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0094] [Example 6] [Production of scandium fluoride particles] A 2 mol / L aqueous solution of scandium nitrate equivalent to 2 mol of scandium nitrate was heated to 50°C, and a 12 mol / L aqueous solution of ammonium fluoride equivalent to 7 mol of ammonium fluoride was added to the heated aqueous solution of scandium nitrate and mixed, and the temperature was maintained at 50°C and stirred for 1 hour. The resulting precipitate was filtered, washed, and then dried at 70°C for 24 hours to obtain a scandium ammonium fluoride double salt. The resulting scandium ammonium fluoride double salt was then fired at 850°C for 2 hours in a tubular furnace under a nitrogen gas atmosphere, and pulverized with a jet mill to obtain scandium fluoride particles.

[0095] [Evaluation of the physical properties of scandium fluoride particles] The physical properties of the yttrium fluoride particles were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0096] [Production of composite particles] Five moles of scandium oxide particles having a cumulative 50% diameter (median diameter) of 1 μm in the volume-based particle size distribution were added to pure water and stirred to prepare a slurry with a scandium oxide particle concentration of 20 mass %. 9 moles of acidic ammonium fluoride were added to the obtained slurry and aged at 50° C. for 3 hours. The obtained particles were filtered, washed, and then dried at 70° C. to obtain composite particles containing scandium oxide and ammonium scandium fluoride double salt.

[0097] [Production of film-forming materials] The scandium fluoride particles produced by the above method and composite particles were mixed in a mass ratio of scandium fluoride particles:composite particles=40:60 to obtain a film-forming material.

[0098] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0099] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0100] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0101] [Example 7] [Production of erbium fluoride particles] A 2 mol / L erbium nitrate aqueous solution equivalent to 2 mol of erbium nitrate was heated to 50°C, and a 12 mol / L ammonium fluoride aqueous solution equivalent to 7 mol of ammonium fluoride was added to the heated erbium nitrate aqueous solution, mixed, and stirred for 1 hour while maintaining the temperature at 50°C. The resulting precipitate was filtered, washed, and then dried at 70°C for 24 hours to obtain an erbium fluoride ammonium double salt. Next, the obtained erbium fluoride ammonium double salt was fired at 900°C for 3 hours using a tubular furnace under a nitrogen gas atmosphere, and then pulverized with a jet mill to obtain erbium fluoride particles.

[0102] [Evaluation of physical properties of erbium fluoride particles] The physical properties of the yttrium fluoride particles were evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0103] [Production of composite particles] Five moles of erbium oxide particles with a cumulative 50% diameter (median diameter) of 2 μm in the volume-based particle size distribution were added to pure water and stirred to prepare a slurry with an erbium oxide particle concentration of 20 mass %. 10 moles of acidic ammonium fluoride were added to the obtained slurry and aged at 50° C. for 3 hours. The obtained particles were filtered, washed, and then dried at 70° C. to obtain composite particles containing erbium oxide and ammonium erbium fluoride double salt.

[0104] [Production of film-forming materials] The erbium fluoride particles produced by the above method and composite particles were mixed at a mass ratio of erbium fluoride particles:composite particles=55:45 to obtain a film-forming material.

[0105] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0106] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0107] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0108] [Comparative Example 1] [Production of composite particles and film-forming materials] Composite particles were obtained in the same manner as in Example 2, and used as a film-forming material.

[0109] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0110] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0111] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0112] [Comparative Example 2] [Production of composite particles and film-forming materials] Composite particles were obtained in the same manner as in Example 1. The obtained composite particles were fired in an atmospheric furnace at 900° C. for 5 hours and then pulverized in a jet mill to obtain particles containing a crystal phase of yttrium oxyfluoride and a crystal phase of yttrium fluoride, which were used as a film-forming material.

[0113] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0114] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0115] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0116] [Comparative Example 3] [Production of yttrium fluoride particles] A 2 mol / L yttrium nitrate aqueous solution equivalent to 2 mol of yttrium nitrate was heated to 50°C, and a 12 mol / L ammonium fluoride aqueous solution equivalent to 7 mol of ammonium fluoride was added to the heated yttrium nitrate aqueous solution, mixed, and the temperature was maintained at 50°C and stirred for 1 hour. The resulting precipitate was filtered, washed, and then dried at 70°C for 24 hours to obtain an yttrium fluoride ammonium double salt. Next, the obtained yttrium fluoride ammonium double salt was fired at 650°C for 2 hours using a tubular furnace under a nitrogen gas atmosphere, and then pulverized with a jet mill to obtain yttrium fluoride particles.

[0117] [Evaluation of physical properties of yttrium fluoride particles] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 1.

[0118] [Production of film-forming materials] The yttrium fluoride particles produced by the above method and yttrium oxide particles having a cumulative 50% diameter (median diameter) in a volume-based particle diameter distribution of 2 μm were mixed in a mass ratio of yttrium fluoride particles:yttrium oxide particles=75:25 to obtain a film-forming material.

[0119] [Evaluation of physical properties of film-forming materials] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 2.

[0120] [Production of film-forming slurry] The same procedure as in Example 1 was followed.

[0121] [Evaluation of the physical properties of slurry for film formation] The experiment was carried out in the same manner as in Example 1. The results are shown in Table 3.

[0122] [Table 1]

[0123] [Table 2]

[0124] [Table 3]

[0125] [Example 8] The surface of an A5052 aluminum alloy substrate measuring 100 mm x 100 mm x 5 mm was degreased with acetone, and one side of the substrate was roughened by blast polishing using a corundum abrasive with a grain size of #150. The coating slurry obtained in Example 1 was used for this substrate, and a thermal spray coating was formed directly on the substrate by atmospheric suspension plasma spraying (SPS), to obtain a thermal sprayed member. The atmospheric suspension plasma spraying was performed using a plasma spraying machine 100HE (manufactured by Progressive) and a thermal spraying material supplying device LiquifeederHE (manufactured by Progressive) under the spraying conditions shown in Table 4, in an atmospheric atmosphere and at normal pressure (the same applies to the following atmospheric suspension plasma spraying).

[0126] The crystal phase of the obtained thermal spray coating was identified by X-ray diffraction (XRD) in the same manner as in Example 1, the crystal structure was analyzed, and the maximum peak of each crystal phase component was identified, and rare earth element oxyfluorides (ROF (R1O1F1), R4O3F6, R5O4F7, R6O5F8, R7O6F9, R 17 O 14 F 23 The integrated intensity value I(ROF) of the maximum peak of the diffraction peaks attributable to rare earth element fluorides, and the integrated intensity value I(RO) of the maximum peak of the diffraction peaks attributable to rare earth element oxides were calculated. From these results, X ROF =I(ROF) / (I(RF)+I(RO)) The value of was calculated. In addition, the oxygen content, film thickness, surface roughness (surface roughness) Ra, and R particle amount were measured. Details of each measurement, analysis, and evaluation will be described later.

[0127] [Example 9] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Example 2 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0128] [Example 10] The surface of an A5052 aluminum alloy substrate measuring 100 mm x 100 mm x 5 mm was degreased with acetone, and one side of the substrate was roughened by blast polishing using a corundum abrasive with a grain size of #150. The granular coating material obtained in Example 3 was used for this substrate, and a thermal spray coating was formed directly on the substrate by atmospheric plasma spraying (APS), to obtain a thermal sprayed member. The atmospheric plasma spraying was performed using a plasma spraying machine F4 (manufactured by Oerlikon Metco) and a thermal spraying material supply device TWIN-10 (manufactured by Oerlikon Metco) under the spraying conditions shown in Table 4, in an atmospheric atmosphere and at normal pressure. The obtained thermal spray coating was measured, analyzed, and evaluated in the same manner as in Example 8. The results are shown in Table 5.

[0129] [Example 11] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Example 4 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0130] [Example 12] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Example 5 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0131] [Example 13] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Example 6 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0132] [Example 14] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Example 7 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0133] [Comparative Example 4] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Comparative Example 1 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0134] [Comparative Example 5] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Comparative Example 2 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0135] [Comparative Example 6] A thermal sprayed coating was formed on a substrate to obtain a thermal sprayed member in the same manner as in Example 8, except that the coating-forming slurry obtained in Comparative Example 3 was used. The obtained thermal sprayed coating was subjected to the same measurements, analyses, and evaluations as in Example 8. The results are shown in Table 5.

[0136] [Table 4]

[0137] [Table 5]

[0138] In the thermal spray coatings obtained in Examples 8 to 14, the X-ray diffraction integral intensity I(ROF) of the maximum peak of the diffraction peak attributed to the rare earth element oxyfluoride (in an example in which two or more compounds are present, the sum of the maximum peak integral intensity values ​​of the diffraction peaks of each of the two or more compounds) was calculated from the maximum peak integral intensity I(RF) of the diffraction peak attributed to the rare earth element fluoride, and the maximum peak integral intensity I(RO) of the diffraction peak attributed to the rare earth element oxide. ROF In these cases, it is found that the main crystal phase of the thermal spray coating is rare earth element oxyfluoride, and the abundance ratio of rare earth element fluoride and rare earth element oxide is low.

[0139] The film-forming materials obtained in Examples 1 to 7 are composed of particles containing a crystalline phase of a rare earth element fluoride and composite particles (particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt, or particles containing a crystalline phase of a rare earth element oxide and a crystalline phase of a rare earth element ammonium fluoride double salt), and the X-ray diffraction integral intensity I(RNF) of the maximum peak of the diffraction peak attributed to the rare earth element ammonium fluoride double salt, the integral intensity I(RF) of the maximum peak of the diffraction peak attributed to the rare earth element fluoride, and the integral intensity I(RO) of the maximum peak of the diffraction peak attributed to the rare earth element oxide are calculated. FO , X F and X O The values ​​are all 0.01 or more. It can be seen that the inclusion of composite particles in the coating material increases the reactivity during the thermal spraying process, making it possible to produce a thermal sprayed coating with a high ratio of rare earth oxyfluoride and low ratios of rare earth fluoride and rare earth oxide without requiring excessive thermal spraying heat.

[0140] On the other hand, the thermal spray coating obtained in Comparative Example 4 has a rare earth oxide as the main phase of the crystal phase of the thermal spray coating, since the material for forming the coating in Comparative Example 1 does not contain particles containing a rare earth oxide crystal phase. In addition, the material for forming the coating in Comparative Example 2 does not contain particles containing a rare earth oxide crystal phase of the thermal spray coating obtained in Comparative Example 5, and in the reaction between the rare earth fluoride and the rare earth oxyfluoride, the rare earth fluoride is not completely consumed, and the production of the rare earth oxide is not suppressed, so that a large amount of unreacted rare earth fluoride remains as the crystal phase of the thermal spray coating, and rare earth oxide is by-produced. In particular, in the material for forming the coating in Comparative Example 2 used in Comparative Example 5, in order to make the main phase of the crystal phase of the thermal spray coating a rare earth oxyfluoride, it is necessary to increase the power of the thermal spray conditions. Furthermore, in the thermal spray coating obtained in Comparative Example 6, since the coating material of Comparative Example 3 did not contain particles containing a crystalline phase of rare earth element ammonium fluoride double salt, the reaction between the rare earth element fluoride and rare earth element oxide did not proceed sufficiently during the extremely short time during the thermal spray process, and a large amount of unreacted rare earth element fluoride and rare earth element oxide remained as the crystalline phase of the thermal spray coating.

[0141] [Measurement of particle size distribution] Particle size distribution was measured by laser diffraction. A laser diffraction / scattering particle size distribution analyzer, Microtrac MT3300EX II (Microtrac Bell, Inc.), was used for the measurement. The sample was poured or dropped into the circulation system of the measuring device so that the concentration index DV (Diffraction Volume), which is suitable for use with the measuring device, was 0.01 to 0.09.

[0142] [Measurement of BET specific surface area] The measurement was performed using a fully automatic specific surface area measuring device, Macsorb HM model-1208 (manufactured by Mountec Co., Ltd.).

[0143] [Measurement of loose bulk density] The measurements were carried out using a Powder Tester PT-X (manufactured by Hosokawa Micron Corporation).

[0144] [Measurement of loss on ignition] A sample of the film-forming material was placed in a platinum crucible and heated in an electric furnace in the atmosphere at 500° C. for 2 hours, and the ignition loss was calculated from the mass of the sample before and after heating.

[0145] [Oxygen content measurement] The measurement was performed by inert gas fusion infrared absorption spectrometry.

[0146] [Measurement of slurry viscosity] The measurements were carried out using a TVB-10 viscometer (manufactured by Toki Sangyo Co., Ltd.) with a rotation speed of 60 rpm and a rotation time of 1 minute.

[0147] [Film thickness measurement] The measurements were made using an eddy current film thickness gauge LH-300J (Kett Electric Laboratory).

[0148] [Measurement of surface roughness (Ra)] The surface roughness was measured using a surface roughness measuring device, HANDYSURF E-35A (manufactured by Tokyo Seimitsu Co., Ltd.).

[0149] [Particle evaluation test (R particle amount)] 20mm×20mm(4cm 2 A test piece of a thermal sprayed member on which a thermal spray coating having a surface area of ​​4 cm2 was formed was immersed in ultrapure water with the thermal spray coating side facing the water surface, and ultrasonic cleaning (output: 200 W, irradiation time: 30 minutes) was performed on the test piece to remove contamination after thermal spraying. Next, the test piece was dried, and then ultrasonic treatment (output: 200 W, irradiation time: 15 minutes) was performed on the test piece with the thermal spray coating side facing the bottom of a 100 ml polyethylene bottle in 20 ml of ultrapure water. After ultrasonic treatment, the test piece was removed, and 2 ml of a 5.3 normal nitric acid aqueous solution was added to the treatment liquid after ultrasonic treatment to dissolve the R particles (particles of rare earth element compounds) contained in the treatment liquid. The amount of rare earth elements (R amount) contained in the treatment liquid was measured by ICP atomic emission spectroscopy, and the surface area (4 cm2) of the thermal spray coating of the test piece was measured. 2The smaller this value, the fewer R particles there are on the surface of the thermal spray coating.

Claims

1. In X-ray diffraction using CuKα rays as characteristic X-rays, the diffraction peak of a crystalline phase detected within the range of diffraction angle 2θ = 10 to 70° is represented by the following formula: X ROF =I(ROF) / (I(RF)+I(RO)) (In the formula, I(ROF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxyfluoride, I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by ROF A thermal spray coating, characterized in that the value of is 1.2 or more and 2.2 or less.

2. The thermal spray coating described in claim 1, characterized in that, among the diffraction peaks of the above-mentioned crystalline phase, a diffraction peak attributable to a rare earth element oxyfluoride, a diffraction peak attributable to a rare earth element fluoride, and a diffraction peak attributable to a rare earth element oxide are detected.

3. In X-ray diffraction using CuKα rays as characteristic X-rays, among the diffraction peaks of the crystalline phase detected within the diffraction angle 2θ range of 10 to 70°, a diffraction peak attributable to a rare earth element oxyfluoride, a diffraction peak attributable to a rare earth element fluoride, and a diffraction peak attributable to a rare earth element oxide are detected, and the following formula is obtained: X ROF =I(ROF) / (I(RF)+I(RO)) (In the formula, I(ROF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxyfluoride, I(RF) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element fluoride, and I(RO) is the integrated intensity value of the maximum peak of the diffraction peaks attributable to the rare earth element oxide.) X calculated by ROF A thermal spray coating, characterized in that the value of is 1.2 or more.

4. 4. The thermal spray coating according to claim 1, wherein the thickness of the coating is from 10 μm to 500 μm.

5. A thermal sprayed member comprising the thermal spray coating according to claim 1 on a substrate.

6. The thermal sprayed member according to claim 5, which is a member for semiconductor manufacturing equipment.

7. (1) A thermal spray material including particles including a crystal phase of a rare earth element fluoride, particles including a crystal phase of a rare earth element oxide, and particles including a crystal phase of a rare earth element ammonium fluoride double salt; (2) A thermal spray material including particles containing a crystal phase of a rare earth element fluoride and particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt; (3) A slurry for thermal spraying, comprising a film-forming material including particles including a crystal phase of a rare earth element fluoride, particles including a crystal phase of a rare earth element oxide, and particles including a crystal phase of a rare earth element ammonium fluoride double salt, and a dispersion medium; or (4) A slurry for thermal spraying comprising a film-forming material including particles containing a crystal phase of a rare earth element fluoride and particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt, and a dispersion medium. A method for forming a thermal sprayed coating, comprising thermally spraying a

8. On the substrate, (1) A thermal spray material including particles including a crystal phase of a rare earth element fluoride, particles including a crystal phase of a rare earth element oxide, and particles including a crystal phase of a rare earth element ammonium fluoride double salt; (2) A thermal spray material including particles containing a crystal phase of a rare earth element fluoride and particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt; (3) A slurry for thermal spraying, comprising a film-forming material including particles including a crystal phase of a rare earth element fluoride, particles including a crystal phase of a rare earth element oxide, and particles including a crystal phase of a rare earth element ammonium fluoride double salt, and a dispersion medium; or (4) A slurry for thermal spraying comprising a film-forming material including particles containing a crystal phase of a rare earth element fluoride and particles containing a crystal phase of a rare earth element oxide and a crystal phase of a rare earth element ammonium fluoride double salt, and a dispersion medium. A method for producing a thermal sprayed member, comprising thermally spraying a thermal spray coating.

Citation Information

Patent Citations

  • Material for spray coating, spray coating film, and member with spray coating film

    JP2016211071A

  • Yttrium fluoride thermal spray material, yttrium oxyfluoride film deposition part, and their manufacturing method

    JP2017082325A

  • Material for spray coating, sprayed coating, and member with sprayed coating

    JP2018076546A

  • Oxy yttrium fluoride thermal spray coating, method for manufacturing the same, and thermal spray member

    JP2018184657A

  • Thermal spray material and method for manufacturing same

    WO2014002580A1